Unusual transformation from refractory anemia to chronic myelomonocytic leukemia: a case report. - Pasquale Niscola (Mediterranean Journal of Hematology and Infectious Diseases)
The transformation from myelodysplastic syndrome (MDS) to chronic myelomonocytic leukemia (CMML) is rarely observed; such occurrence have been reported in cases of refractory anemia with ring sideroblasts (RARS)  and  of refractory anemia with excess of blasts (RAEB). Moreover, MDS patients may present monocytosis not fulfilling the diagnostic criteria of CMML, portraying this finding a challenge in diagnosis and classification of these atypical mixed disorders. These problems of diagnostic classification and prognostic stratification may be a concern in the decision-making, particularly in the new era of effective disease-modifying therapies, such as hypomethylating agents6,7. These concerns we have recently encountered in the management of a patient who developed CMML seven years after the diagnosis of refractory anemia (RA). The full clinical onset of CMML was preceded by a progressive loss of response to the ongoing treatment with an erythropoesis stimulating agent (ESA), worsening anemia, thrombocytopenia, leukocytosis and increasing monocytosis. The morphological findings of peripheral blood (PB) and bone marrow (BM) revealed the coexistence of myelodysplastic and myeloproliferative pictures; a cytogenetic alteration (45, X0,-Y), which was not present at diagnosis of RA seven years before, was also detected at the CMML phase. The patient received azacitidine and achieved a good response. We report this case or its rarity and for the implications for disease classification and management.